The Postgraduate Supervisor Under Scrutiny: An Autoethnographic Inquiry - Lemmer, Eleanor M. (Qualitative Sociology Review, 2016)
Effective postgraduate supervision is a critical indicator of individual scholarship and institutional reputation. This paper uses autoethnography to scrutinize critical moments in the author’s enactment of the supervisory role over a lengthy career at a distance education university, where supervision takes place through face-to-face consultation, distance education, or a combination of both modes. Autoethnography, an innovative addition to the compendium of qualitative research methods, is gaining prominence as a means of examining the academic life through the personal and professional histories of individual academics. The author’s aim is to focus both inward on the vulnerable self as expressed in the role of academic supervisor and outward on the social and cultural aspects of this role as it is shaped within the context of the university. This has been done by constructing a text with a high degree of self-reflexivity, which combines evocative and literary elements with some explicit theorizing around generativity theory. Generativity is defined as an adult’s concern for and commitment to promoting the well-being of the next generation, in this case, the intellectual well-being of future cohorts of scholars. Against the framework of generativity, a series of autobiographical vignettes illustrate self-defining moments in the author’s development as supervisor. The role of memory and memory supports in producing an accurate story and measures taken to interact with the characters in the stories to enhance textual credibility are addressed. The vignettes illustrate the desire to conduct supervision as a generative act; cultural demand for generativity; the transmission of a personal aesthetic in supervision; the separation-individuation of the student; the redemption of generative commitment in the face of threats to generativity; and the perpetuation of the generative cycle. I conclude that autoethnography as method presents a useful route to both self-understanding and social understanding of the academic life, with particular reference to the role of postgraduate supervisor.